2014
DOI: 10.1063/1.4902316
|View full text |Cite
|
Sign up to set email alerts
|

Doping dependence and anisotropy of minority electron mobility in molecular beam epitaxy-grown p type GaInP

Abstract: Direct imaging of minority electron transport via the spatially resolved recombination luminescence signature has been used to determine carrier diffusion lengths in GaInP as a function of doping. Minority electron mobility values are determined by performing time resolved photoluminescence measurements of carrier lifetime on the same samples. Values at 300 K vary from ∼2000 to 400 cm2/V s and decrease with increasing doping. Anisotropic diffusion lengths and strongly polarized photoluminescence are observed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Figure shows the results of Hall effect measurements for InGaP and AlGaAs layers. We see a decreasing mobility as a function of doping, typical of free majority and minority carrier mobility trends and comparable with other values reported in the literature . Thus, to optimize solar cell performances, the choice of a low p‐type doping level should ensure good minority and majority carrier mobilities.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Figure shows the results of Hall effect measurements for InGaP and AlGaAs layers. We see a decreasing mobility as a function of doping, typical of free majority and minority carrier mobility trends and comparable with other values reported in the literature . Thus, to optimize solar cell performances, the choice of a low p‐type doping level should ensure good minority and majority carrier mobilities.…”
Section: Resultssupporting
confidence: 87%
“…Dashed arrows are guides to the eyes. Majority carrier mobilities taken from the literature are from Shitara et al, Liu et al, and Blood et al *Mobility of minority carriers are also taken from Haegel [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…It is known that the material quality of p-InGaP for solar cell application is limited by carrier mobilities and the choice of dopants. In fact, cracked phosphorous used in MBE growth induces a significant n-type residual doping, up to 1e16 cm -3 , limiting the control of low p-type doping levels in InGaP structures to concentrations higher than ~1e17 cm-3, thus decreasing carriers mobilities, as seen previously by Haegel et al and confirmed by Hall effect measurements [17].…”
Section: A Algaas and Ingap Solar Cellsmentioning
confidence: 53%
“…This allows direct visualization of carrier diffusion, drift, or luminescent coupling, i.e., any process that results in photon emission at a location is spatially removed from the point of excitation. Since it gives direct access to the transport of minority carriers in doped semiconductor materials, transport imaging with far-field collection has most recently been used to measure minority carrier diffusion lengths and associated minority carrier mobilities in GaInP as a function of both doping and temperature [2], [3]. This was accomplished by studying specially designed double heterostructures of GaInP, which is the top cell material in the highest efficiency multijunction devices, and imaging resulting transport in the plane.…”
Section: Introductionmentioning
confidence: 99%